2016
DOI: 10.1136/bmjopen-2016-013774
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre, prospective, randomised, open-label, blinded end point trial of the efficacy of allopurinol therapy in improving cardiovascular outcomes in patients with ischaemic heart disease: protocol of the ALL-HEART study

Abstract: IntroductionIschaemic heart disease (IHD) is one of the most common causes of death in the UK and treatment of patients with IHD costs the National Health System (NHS) billions of pounds each year. Allopurinol is a xanthine oxidase inhibitor used to prevent gout that also has several positive effects on the cardiovascular system. The ALL-HEART study aims to determine whether allopurinol improves cardiovascular outcomes in patients with IHD.Methods and analysisThe ALL-HEART study is a multicentre, controlled, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 32 publications
0
60
0
3
Order By: Relevance
“…Results of a large-scale trial (the ALL-HEART Study) are also awaited to assess potential allopurinol CV end point and mortality benefits in subjects without gout. In that study, allopurinol 600 mg/day is added to therapeutic regimens for patients with ischemic heart disease (31). The ongoing VA STOP GOUT comparative effectiveness RCT of allopurinol versus febuxostat does not appear likely to meaningfully impact the interpretation of the CARES results, since gout flare rate is the primary end point of VA STOP GOUT, and the study is not specifically powered to evaluate CV event risk (32).…”
Section: Strengths Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a large-scale trial (the ALL-HEART Study) are also awaited to assess potential allopurinol CV end point and mortality benefits in subjects without gout. In that study, allopurinol 600 mg/day is added to therapeutic regimens for patients with ischemic heart disease (31). The ongoing VA STOP GOUT comparative effectiveness RCT of allopurinol versus febuxostat does not appear likely to meaningfully impact the interpretation of the CARES results, since gout flare rate is the primary end point of VA STOP GOUT, and the study is not specifically powered to evaluate CV event risk (32).…”
Section: Strengths Of the Studymentioning
confidence: 99%
“…Third, more evidence now exists to support allopurinol as a relatively safe urate-lowering drug when risk factors for allopurinol hypersensitivity syndrome are taken into appropriate consideration (35). Fourth, there is increased evidence of clinical efficacy and safety of allopurinol dose escalation in gout, commonly reaching doses >300 mg/day, and operable in the subset of patients with stage 3 chronic kidney disease (31,(36)(37)(38). Fifth, allopurinol dose escalation was effective in the majority of patients with gout in a recent RCT (34).…”
Section: Strengths Of the Studymentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Inconsistencies may be because of variability in sample size, study design and approaches used to account for biases. 22 The potential impact of allopurinol in diabetes is of particular importance because individuals with diabetes are more likely to have hyperuricaemia and are at higher risk of cardiovascular events and death. 20 In a recent clinical trial evaluating the cardiovascular safety of febuxostat, a non-purine xanthine oxidase inhibitor, compared with allopurinol, all-cause and cardiovascular-specific mortality were lower in subjects treated with allopurinol.…”
Section: Introductionmentioning
confidence: 99%
“…21 The ALL-HEART study, which is currently ongoing, is evaluating allopurinol compared with placebo in 5215 subjects with ischaemic heart disease. 22 The potential impact of allopurinol in diabetes is of particular importance because individuals with diabetes are more likely to have hyperuricaemia and are at higher risk of cardiovascular events and death. 23,24 While some studies have showed improved endothelial function and reduced oxidative stress in response to allopurinol in subjects with diabetes, results have not been consistent and may be dose dependent.…”
Section: Introductionmentioning
confidence: 99%
“…In the ongoing Aspirin Dosing: A Patient-centric Trial Assessing Benefits and Long-term Effectiveness (ADAPTABLE) study, a streamlined webbased trial comparing two doses of aspirin in people with prior cardiovascular disease, vascular and bleeding events are assessed from participant reports supplemented by routine hospital claims data, with further investigation reserved for those events where a discrepancy exists [32]. However, future trials in countries with a single health provider or with good record linkage systems could potentially rely entirely on linkage to the EHRs, as is planned for an ongoing trial of allopurinol vs placebo in 5000 people with ischaemic heart disease in the UK [33]. Systems developed by regulatory agencies to link large numbers of health datasets for post-marketing surveillance, such as the EU-ADR web platform [34] and the FDA Sentinel Initiative [35], could be used to obtain outcomes for trials and embedded randomised trials are already part of the FDA Sentinel Initiative [35].…”
Section: Run-in Periodmentioning
confidence: 99%